Kekayaan Intelektual sebagai Aset Perusahaan: Konstruksi Hukum Perlindungan dan Komersialisasi di Indonesia - Tata Eliestiana Dyah. A; Burhanudin; Al Pyan Syah Marszedi (RETORIKA: Journal of Law, Social, and Humanities, 2026)
This study aims to analyze the status of intellectual property as a corporate asset and formulate the legal framework for its protection and commercialization in Indonesia. This study uses normative legal research with a statutory and conceptual approach. The legal materials consist of primary, secondary, and tertiary legal materials collected through literature review and analyzed using legal interpretation, legal theory, and legal principles. The results of the study indicate that intellectual property can be considered a corporate asset as long as it is acquired or controlled based on a valid legal basis, has clear ownership status, and has economic value for the company. Intellectual property protection is necessary to maintain exclusive rights and prevent unauthorized use, while commercialization can be carried out through direct use, transfer of rights, or licensing in accordance with the characteristics of each type of intellectual property. The legal framework for protection and commercialization requires integration between intellectual property law and corporate law through clarity of ownership, protection of rights, and optimization of economic use. This framework can strengthen legal certainty and support the value and competitiveness of companies in Indonesia